Gender, Independensi Penampilan (IN - APPEARANCE), Pengalaman, Self-Efficacy dan Kinerja Auditor dalam Pembuatan Audit Judgement - Dewi Maharani Kartika Untari; Sigit Handoyo (Jurnal Aplikasi Bisnis, 2017)
This study aims to test effect of gender, independence in appearance, experience, and self effiicacy on performance of auditors in making audit judgement. Sample of this study is auditor from audit firm in Yogyakarta and Solo. The instrument of this study is questionnaire which distributed directly to auditors. Data analysis with SPSS 17. The results show that gender, independence in appearance, and self-efficacy have an effect in making audit judgement.